JASALMA INTELLEKT (AI) ORTALÍǴÍNDA IOT MAǴLÍWMATLARÍN GOMOMORFIKALÍQ ShIFRLAW ALGORITMLERI TIYKARÍNDA QORǴAW - Saparniyazov, Berdax Abdirazakovich; Saymanov, Islambek Mirzabaevich; Bazarbaev, Axmet Qidirbayevich; Shaniyazova, Nesibeli Userbayevna (ILIM hám JÁMIYET, 2026)
This paper investigates the preservation of data privacy generated by Internet of Things (IoT) devices during processing within artificial intelligence (AI) environments. To ensure the security of IoT data, homomorphic encryption (HE) algorithms (PHE, SHE, FHE) are analyzed. The mechanisms for executing mathematical operations on encrypted data within AI models (using linear regression as an example) are studied using Paillier, BFV, and CKKS schemes. The models are compared based on accuracy, computational latency, and memory overhead, and the most efficient algorithm is selected.